Climate-Friendly Commodity : A Glimpse on the Potential of Theobroma Cacao L. In Storing Carbon - Nurafiza, Aman; Mohd Effendi, Wasli; Siti Nurbaidzuri, Reli @ Raily; Sharifah Mazenah, Wan Yusuf (Springer Nature Singapore Pte Ltd., 2025)
Within agriculture ecosystems, the five main carbon pools are soils, belowground biomass, deadwood, litter, and aboveground biomass, which become the biggest percentage of carbon stock contributions. However, minimal data were recorded on potential carbon stored within Malaysia’s aboveground biomass of cocoa trees. This study aimed to determine carbon stock potential using the destructive sampling method of six main compartments of Theobroma cacao L. biomass: leaves, branches, main stem, cocoa pods, taproot, and fibrous root. Four sample plots (40 × 5 m) within a hectare of cocoa area in Serian, Sarawak (0° 53 7 N, 110° 35 19 E) were established. Freshly cut samples were taken to Soil Laboratory of the Faculty of Resource Science and Technology, UNIMAS for carbon determination using Elemental CHN Analyzer LCHN-A11 for every tree compartment. Results showed that wooded compartments stored the highest carbon percentage compared to nonwoody compartments; taproot stored the highest carbon with 42.6% followed by the main stem, branches, fibrous root, pod, and leaves with 41.7%, 41.6%, 41.5%, 33.4%, and 32.5%, respectively. These data suggest that cocoa trees do have the potential to help mitigate carbon emissions by storing them in their standing biomass. Data obtained are essential for strategizing possible policies for the cocoa sector in sustaining the environment as stated under National Factor Area 2030.